Analysis of an SEIR-SEI four-strain epidemic dengue model with primary and secondary infections - Isea, Raúl (Conocimiento Libre y Licenciamiento (CLIC), 2014)
We propose an SEIR model for the populations and an SEI model for the vector to describe the transmissiondynamics of a four-strain model with both primary and secondary dengue infections. In order to accomplish this, we propose and obtain an analytic solution of a system of 47 coupled differential equations. This would be the most complete epidemic model proposed to describe the dengue epidemic.